Brave explorer - Florence, Debbi Michiko (Florence, Debbi Michiko. Jasmine Toguchi., 2022)
Eight-year-old Jasmine is enthusiastic about her family's vacation to Japan, but once in Tokyo she is distracted by her older sister's grumpiness and her own blunders--will she be able to cheer up her sister while finding her own footing? Includes author's note and recipe.